A low muscle mass increases mortality in compensated cirrhotic patients with sepsis. (10th February 2018) - Lucidi, Cristina; Lattanzi, Barbara; Di Gregorio, Vincenza; Incicco, Simone; D'Ambrosio, Daria; Venditti, Mario; Riggio, Oliviero; Merli, Manuela
Abstract: Background & Aims: Severe infections and muscle wasting are both associated to poor outcome in cirrhosis. A possible synergic effect of these two entities in cirrhotic patients has not been previously investigated. We aimed at analysing if a low muscle mass may deteriorate the outcome of cirrhotic patients with sepsis. Methods: Consecutive cirrhotic patients hospitalized for sepsis were enrolled in the study. Patients were classified for the severity of liver impairment (Child‐Pugh class) and for the presence of "low muscle mass" (mid‐arm muscle circumference<5th percentile). The development of complication during hospitalization and survival was analysed. Results: There were 74 consecutive cirrhotics with sepsis. Forty‐three of these patients showed low muscle mass. In patients with and without low muscle mass, severity of liver disease and characteristics of infections were similar. Mortality tended to be higher in patients with low muscle mass (47% vs 26%, P  = .06). A multivariate analysis selected low muscle mass ( P  < .01, HR: 3.2, IC: 1.4‐4.8) and Child‐Pugh C ( P  < .01, HR: 3.3, 95% IC: 1.5‐4.9) as independent predictors of in‐hospital mortality. In Child‐Pugh A‐B patients, mortality was higher in patients with low muscle mass compared with those without (50% vs 16%; P  = .01). The mortality rate and the incidence of complications in malnourished patients classified in Child‐Pugh A‐B were similar to those Child‐Pugh C. Conclusions: Low muscle mass worsen prognosis in cirrhotic patients with severe infections. This is particularly evident in patients with Child A‐B cirrhosis in whom the coexistence of low muscle mass and sepsis caused a negative impact on mortality similar to that observable in all Child C patients with sepsis. Abstract : See Editorial on Page786